Bioactives and their roles in bone metabolism of osteoarthritis: evidence and mechanisms on gut-bone axis - Basak, Sanjay; Hridayanka, Kota Sri Naga; Duttaroy, Asim K. (Frontiers in Immunology, 2024)
Bioactives significantly modify and maintain human health. Available data suggest that bioactives might play a beneficial role in chronic inflammatory diseases. Although promised, defining their mechanisms and opting to weigh their benefits and limitations is imperative.Detailed mechanisms by which critical bioactives, including probiotics and prebiotics such as dietary lipids (DHA, EPA, alpha LA), vitamin D, polysaccharides (fructooligosaccharide), polyphenols (curcumin, resveratrol, and capsaicin) potentially modulate inflammation and bone metabolism is limited. Certain dietary bioactive significantly impact the gut microbiota, immune system, and pain response via the gut-immune-bone axis. This narrative review highlights a recent update on mechanistic evidence that bioactivity has been demonstrated to reduce osteoarthritis pathophysiology.